Typology jihatul ka’bah on qibla direction of Mosques in Semarang - Ahmad Izzuddin (Sultang Agung Islamic University, 2020)
Indonesia is the country with the largest number of Muslims in Southeast Asia. The development of celestial science in perfecting worship also contributed to the implementation of integration between religious science and science contained in the concept of jihatul ka'bah. Including improving the measurement of the Qibla direction in Indonesian society which in the last year was quite widespread, especially in Semarang, Central Java. This research is a type of field research with objects of mosques in the city of Semarang. Data analysis techniques using astronomical theory is spherical trigonometry. The results of this study conclude two things. First, the direction of the subdistrict mosque in the city of Semarang is included in the accurate category. Based on the results of measurements of 15 mosques, only 3 mosques have the greatest deviation between 1 to 12 degrees. Second, the implementation of the Jihatul Kaaba as a form of integration of religion and science can be seen in the efforts of the Semarang city community in measuring the direction of Qibla by being open in accepting the results of corrections to the latest Qibla direction measurement.